Subservience [videorecording (DVD)] - Dale, S. K.; Palmer, Jed (Film composer); Fox, Megan, 1986-; Morrone, Michele; Zima, Madeline (Decal, 2024)
"Alice is a lifelike artificially intelligent android, who has the ability to take care of any family and home. Looking for help with the housework, a struggling father purchases Alice after his wife becomes sick. Alice suddenly becomes self-aware and wants everything her new family has to offer, starting with the affection of her owner--and she'll kill to get it"--